A Comparison of EORTC And CUETO Risk Tables in Terms of the Prediction of Recurrence and Progression in All Non-Muscle-Invasive Bladder Cancer Patients - Dalkilic, Ayhan; Bayar, Goksel; Kilinc, Muhammet Fatih (Urology Journal, 2019)
Purpose: To compare the prediction accuracy of the European Organization for Research and Treatment of Cancer (EORTC) and the Spanish Urology Association for Oncological Treatment (CUETO) risk tables in all non-muscle invasive bladder cancer patients. Material and Methods: Recurrence and progression-free survival of all patients were assessed according to the EORTC and the CUETO risk tables for each patient and the concordance index was used to indicate discriminative ability. Statistical analyses were performed, at 1 and 5 years, to the whole group and separately to those treated or not treated with bacillus Calmette-Guerin (BCG) . Results: The study included 400 patients. One-year BCG maintenance therapy was applied to 181 patients (45.3%). The recurrence rate was higher than in CUETO, and similar to EORTC. The EORTC was determined to provide better discrimination than CUETO in the whole patient group and in those treated or not treated with BCG. The concordance indices for these groups were 0.777, 0.705; 0.773, 0.669; and 0.823, 0.758, respectively . The progression rate was similar in this study to the rate defined in both risk tables. The discrimination power was similar in EORTC and CUETO for all the groups. The concordance indices were 0.801, 0.881; 0.915, 0.930; and 0.832, 0.806, respectively. Conclusion: The EORTC has more power than CUETO to discriminate each recurrence risk group and both risk tables can successfully discriminate progression risk groups in all patients.